INTEGRASI FINTECH SYARIAH BERBASIS ESG TERHADAP KEBERLANJUTAN UMKM HALAL DI INDONESIA: PERSPEKTIF MAQASHID SYARIAH - Ade Ruslan Hidayat; Linda Hindriana; Risna Nurul Insani; Regina Maurizka Rifada; Wida Hartika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the integration of Sharia-based financial technology (Fintech) with ESG (Environmental, Social, and Governance) principles to support the sustainability of halal MSMEs (Micro, Small, and Medium Enterprises) in Indonesia from the perspective of Maqashid Sharia. The research addresses the challenges faced by halal MSMEs in accessing financial resources, adopting sustainable practices, and complying with ethical and Sharia standards. The study aims to analyze how ESG-based Fintech solutions can enhance business continuity, financial inclusion, and ethical compliance of halal MSMEs. A qualitative approach was employed, combining literature review, case studies of selected halal MSMEs, and in-depth interviews with stakeholders, including business owners, Fintech providers, and regulatory authorities. The results indicate that integrating Sharia Fintech with ESG principles contributes positively to the long-term sustainability of halal MSMEs by providing easier access to compliant financing, promoting responsible business practices, and aligning operational goals with Maqashid Sharia values. Furthermore, stakeholders perceive that ESG-oriented Fintech platforms enhance trust, improve risk management, and strengthen social and Environmental responsibility within halal business ecosystems. The study concludes that the integration of Sharia Fintech and ESG frameworks is an effective strategy for fostering resilient and sustainable halal MSMEs in Indonesia, offering implications for policymakers, practitioners, and investors seeking to support ethical and sustainable entrepreneurship.